Islamic Financial Model: the Problems of Formation and the Demand for Development in Russia in the Current Political and Economic Situation - I. A. Zaripov (Мир новой экономики, 2023)
In the current severe political and economic situation, Russia radically needs revising its development strategy, finding truly reliable and long-term partners. Among the most preferred counterparts for building long-term mutually beneficial relations are the Islamic states, which prefer to use a financial model complaint with their confessional principles. The Islamic financial model is relevant for Russia not only as a tool to attract Islamic investments, but also as a framework for building strong relations with most solid partners. Despite the fact that the Islamic financial model is criticized from the inside, and not devoid of certain shortcomings, the principles laid down in it will be able to ensure the even development of the economy and reduce social tensions through a fair redistribution of income. This article tells about the development of Islamic finance in the world and in Russia.